2021
DOI: 10.3390/ijms22042050
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Understanding of the Copper Homeostasis in Pseudomonas aeruginosa

Abstract: Thirty-five thousand people die as a result of more than 2.8 million antibiotic-resistant infections in the United States of America per year. Pseudomonas aeruginosa (P. aeruginosa) is classified a serious threat, the second-highest threat category of the U.S. Department of Health and Human Services. Among others, the World Health Organization (WHO) encourages the discovery and development of novel antibiotic classes with new targets and mechanisms of action without cross-resistance to existing classes. To fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 187 publications
2
16
0
Order By: Relevance
“…At higher Cu(I) concentrations, inhibition of this process occurs, previously reported as a “dead‐end” state by smFRET experiments 16 . Therefore, at higher copper concentrations, alternative copper regulation mechanisms controlled by other copper regulators could reduce prolonged and elevated copper levels 2 …”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…At higher Cu(I) concentrations, inhibition of this process occurs, previously reported as a “dead‐end” state by smFRET experiments 16 . Therefore, at higher copper concentrations, alternative copper regulation mechanisms controlled by other copper regulators could reduce prolonged and elevated copper levels 2 …”
Section: Discussionmentioning
confidence: 85%
“…16 Therefore, at higher copper concentrations, alternative copper regulation mechanisms controlled by other copper regulators could reduce prolonged and elevated copper levels. 2 In our previous studies, 17,18 we also hypothesized that there is more than one Cu(I) binding site in CueR. Recently, Balogh et al 42 explored the binding of Hg(II) to CueR and suggested that the last seven residues at the Cterminal tail of CueR form a second metal ion binding site with C129 and C130 coordination.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Considering the ubiquitous presence of metals in the cell, it follows that even small errors in biometal regulation are likely to impact cell function, growth, and survival. It is, thus, of tremendous importance to understand each step in the cycle of metal uptake, usage, and clearance to achieve a fundamental understanding of the sources of metal homeostasis disruption [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, we have been applying EPR spectroscopy to However, in prokaryotic systems, copper regulation is more sophisticated, since such microorganisms can encounter changes in their environment. In Gram-negative bacteria, four different mechanisms regulate cellular Cu(I) (Figure 1B) [10]. The first mechanism involves proteins that export copper from the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%